Growth Analysis of Differences in Shallot (Allium ascalonicum L.) Seedling Size - Wahyu Arsadiarta, I Gusti Ngurah; Wijana, Gede; Gunadi, I Gusti Alit (Universitas Panji Sakti, 2024)
Choosing the right seed size is essential in shallot cultivation. Using good-quality seeds will increase the growth of shallots. Through growth analysis of various sizes of shallot seedlings, information will be obtained about the growth potential of shallots. This research aims to compare the growth patterns of shallot seedlings of varying sizes. The research was carried out from August to September 2023 at Br. Aseman, Sedang Village, Abiansemal District, Badung Regency, Bali and at the Plant Breeding and Seed Technology Laboratory, Faculty of Agriculture, Udayana University, Denpasar. This research used a one-factor randomized block design (RBD) with different treatment sizes of shallot seedlings, namely 3 g, 5 g, 7 g, 9 g, and 11 g. Each treatment was repeated 5 times, yielding 25 experimental units. The results showed that differences in the size of shallot seedlings very significantly influenced the initial growth of the seedlings (3-15 DAP). The heavier the weight of the shallot seeds, the higher the growth of the shallots. The plant growth analysis metrics, relative growth rate and net assimilation rate, reveal that the results do not differ significantly across observation time intervals. The treatment using seed size 11 g showed the highest increase in each parameter compared to other treatments at each observation time interval.